Comparison of different cement application techniques for tibial component fixation in TKA - Schlegel, Ulf J.; Bishop, Nicholas; Püschel, Klaus; Morlock, Michael; Nagel, Katrin (International orthopaedics, 2015)
PURPOSE: Aseptic loosening of the tibial component remains a major cause for revision surgery in total knee arthroplasty (TKA). A stable initial fixation of the tibial implant has been suggested to reduce micromotion of the implant and could be decisive regarding its long-term performance. Different techniques for applying cement to the tibial surface have been described in the literature, with controversial results. No guidelines in favour of any particular approach are available. - METHODS: In this study, we compared three commonly used cementing techniques (layered application, stem cementation, cement gun) with surface-only fingerpacking cementation following pulsed lavage (paired human tibiae, four groups, n = 24). Specimens underwent computed tomography scanning for three-dimensional analysis of cement penetration and mechanical testing for assessing interface strength. - RESULTS: Bone cement penetration decreased with increasing bone mineral density (BMD) (R (2) = 0.18, p = 0.023), while interface strength increased with BMD (R (2) = 0.56, p < 0.001). No significant effect of cementation techniques on cement penetration (p ≥ 0.069) or interface strength (p = 0.180) was found in any group. - CONCLUSION: Adequate surface preparation using pulsed lavage and copious drying of the tibial surface appears to be of overruling importance, thus limiting the effect of any particular technique applied to improve implant fixation. This study emphasises the fundamental importance of surface preparation and pulsed lavage in TKA.
Published online: 1 August 2014
Gesehen am 25.06.2020